(untitled) (Shanti Journal, 2024)
Welcome to Shanti Journal: A Multidisciplinary Journal! Published bi-annually by Research Management Cell of Bishwa Shanti Chiran Milan Campus, Shanti Journal aims to provide a platform for researchers and scholars to publish their work in various disciplines relating to arts and humanities. Our journal covers a wide range of topics, including language, literature, culture, international relations, performance arts, media, and communication. Shanti Journal seeks to promote original and high-quality research in both empirical and theoretical domains. We welcome submissions that present previously unpublished work, including research results, case studies, and theoretical analyses. It is important to note that all articles submitted to our journal should not be under consideration for publication elsewhere. To ensure the quality and integrity of the articles published in Shanti Journal, all submissions undergo a rigorous peer review process. Our team of expert reviewers evaluates each submission based on its originality, methodology, significance, and adherence to academic standards. The review process helps us maintain the highest standards of scholarly excellence. Shanti Journal encourages academic writing and publication across a wide range of specializations within the academic and research domains. Our journal covers diverse topics, including but not limited to: Gender studies, Children’s rights, Media studies, Social and cultural sustainability, Domestic and global issues, Education, Health risks, Environmental management, Literature. We believe that by encompassing such a broad focus, Shanti Journal can contribute to the advancement of knowledge and understanding in various fields. We would like to express our sincere appreciation to all the authors who have contributed their insightful work to Shanti Journal. Your dedication to research and scholarship is invaluable, and we are honored to showcase your contributions. We would also like to extend our gratitude to our distinguished reviewers. Your expertise and support during the review process have been instrumental in maintaining the quality of the journal. We are grateful for your commitment to academic excellence. As the Editor-in-chief of Shanti Journal, I am proud to lead a team that is dedicated to promoting multidisciplinary research and academic writing. Our mission is to foster excellence in scholarly work and contribute to the advancement of knowledge in various disciplines relating to arts and humanities. Thank you for your continued support and interest in Shanti Journal.